Gambaran Media Dan Bangunan Rumah Penderita Tuberkulosis Paru Di Wilayah Kerja Puskesmas Gedong Air Kota Bandar Lampung Tahun 2026 - Hervina Sari; Mei Ahyanti; Karbito Karbito (STIKES Columbia Asia Medan, 2026)
Pulmonary tuberculosis (TB) remains a communicable disease and a major public health problem in Indonesia. The media and building conditions of houses occupied by pulmonary tuberculosis patients play an important role in the transmission of this disease. This study aimed to describe the media and building conditions of houses occupied by pulmonary tuberculosis patients in the Working Area of Gedong Air Public Health Center, Bandar Lampung City, in 2026, covering occupancy density, bedroom lighting, bedroom humidity, bedroom temperature, and bedroom ventilation rate. This study employed a quantitative descriptive design with an observational approach. A total of 60 houses of pulmonary tuberculosis patients were selected using a simple random sampling technique. Data were collected through observation and interviews and were analyzed using univariate analysis. The results showed that most of the media and building conditions of houses occupied by pulmonary tuberculosis patients did not meet health requirements in terms of occupancy density, bedroom lighting, bedroom humidity, bedroom temperature, and bedroom ventilation rate. It can be concluded that the media and building conditions of houses occupied by pulmonary tuberculosis patients in the Working Area of Gedong Air Public Health Center, Bandar Lampung City, in 2026 were predominantly not in accordance with healthy housing requirements. Therefore, education for patients and their families regarding health-compliant media and building requirements, particularly related to occupancy density, bedroom lighting, bedroom humidity, bedroom temperature, and bedroom ventilation rate, is needed to help reduce the risk of pulmonary tuberculosis transmission.